Root Plasticity Not Evident in N-Enriched Soil Volumes for Wheat (Triticum aestivum L.) and Barley (Hordeum vulgare L.) Varieties. Issue 17 (25th September 2017) - Rabbi, Sheikh M. F.; Guppy, Chris; Flavel, Richard; Tighe, Matthew; Young, Iain
ABSTRACT: Root plasticity is a unique characteristic of root systems that may enhance the nutrient foraging capacity of plants. Here we investigated the effect of localized high nitrogen (N) concentration on plasticity of wheat and barley roots in soil. We conducted a series of experiments to maintain localized high concentration of N in soil and to evaluate any root morphological variation in the enriched N zone. Wheat and barley seedlings were grown in N responsive Red Ferrosol with an enriched subsurface N band for 12 days. Wheat and barley roots did not proliferate in N-enriched soil volumes. Rather, higher root length density ( 1.6 times) was observed in low N surface soil. Shoot dry matter and shoot N uptake of banded N treatment was statistically similar between uniform and low N treatments. Results indicated the absence of plastic root response of the wheat and barley seedlings in subsurface N band.